Caecal volvulus: ten year experience in an Australian teaching hospital. - Neil, D. A. (Royal College of Surgeons of England, 1987)
Sixteen cases of caecal volvulus were treated surgically at a major Australian teaching hospital over a decade. Review of these cases suggests that this condition may be more common in fit people between 30 and 40 years of age than in the elderly or institutionalised. Caecal volvulus was more common in women than in men, possibly because adhesions from previous gynaecological surgery may initiate volvulus. In some other cases colonic distension due to poor muscle tone rather than distal obstruction may have been an important predisposing factor. Preoperative diagnosis was not usually made, but might have been facilitated if knowledge of the above predisposing factors had been available. This would allow colonoscopic reduction to be considered as a therapeutic alternative to laparotomy. At laparotomy, right hemicolectomy or caecal fixation (caecostomy or caecopexy) were the alternative methods of treatment.